Voragocoris weirauchae sp. n. (Heteroptera: Schizopteridae: Schizopterinae), a further minute litter bug species from Brazil - de Albuquerque Almeida, Flavio Roberto; Carvalho-Filho, Fernando Da Silva; Knyshov, Alexander; Fernandes, Jose Antonio Marin (Zootaxa, 2020)
The genus Voragocoris Weirauch, 2012 is composed of Voragocoris schuhi Weirauch, 2012 and Voragocoris amrishi Makhan, 2013, previously recorded from Peru and Suriname, respectively. In this paper, a new species, Voragocoris weirauchae sp.n., is described based on specimens collected in the Brazilian Amazon, representing the first record of the genus from Brazil. We provide diagnosis, description, photographs of habitus, and scanning electron micrographs of the diagnostic features. A key to species based on males of Voragocoris is also presented.